The Influence Of Leadership And Work Motivation On Employee Performance At The Hotel Harris Sentraland Semarang - Sugiyati, Eka Octa Amelia; Aswan, Mukhamad Kholil (International Journal on Social Science, Economics and Art, 2024)
This study is an effort to analyze the influence of leadership and work motivation on employee performance at Harris Sentraland Hotel Semarang. Data were collected through questionnaires distributed to 70 hotel employees. The data analysis method used is multiple linear regression analysis using SPSS software. The results showed that leadership and work motivation have a positive and significant effect on employee performance. This means that the better the leadership and work motivation provided, the more employee performance will improve. The implication of this research is that hotel management needs to pay attention to aspects of leadership and work motivation to improve employee performance, such as providing leadership training to managers and holding programs that can motivate employees at work.